KONSEP KEMBALI KEPADA AL-QUR’AN DAN HADIS - Muhammad Khoiruzzadi (stit-islamic-village, 2021)
The concept of returning to the Al-Qur'an and hadith is always interesting to talk about, both among scholars and lay people. This article aims to find out the dangers of returning to the Qur'an and hadith with translation, the occurrence of differences of opinion among the scholars, and the correct understanding of the Koran and hadith, as well as textual and contextual understanding of the Qur'an. The type of writing of this article is the library research method with the variables being Al-Qur'an, hadith, ikhttilaf and tafsir. The result of the discussion in this article is that it takes quite a long time to understand one difference if you really want to look for the verses of the Al-Qur'an and hadiths that discuss these differences yourself. In addition to having good Arabic language provisions, other knowledge is also needed in understanding the Qur'an so that ulumul quran and understanding hadith (ulumul hadith) emerge. Not to mention the good interpretation of the Al-Qur'an and syarah traditions which need to be used as guidance when trying to understand a verse or hadith. Differences in a case result in different laws and different behavior. This difference is a necessity that has been established by Allah SWT. In understanding the Qur'an, there are those who understand it textually and contextually. The textual understanding of the text is subject to the claim of orthodoxy and the validity of its interpretation, and this leaves only a small space for the exegete to critically dwell on the sides of contextual revelation. The contextual approach is an approach that tries to interpret the Qur'an based on considerations of language analysis, historical background, sociology, and anthropology that prevailed in the life of pre-Islamic Arab society and during the process of revelation of the Qur'an. Next, we will explore the moral principles contained in various approaches.